Eligibility for Second-line Therapy in Patients With Advanced Hepatocellular Carcinoma: A Population-based Study. (November 2020) - Tsang, Erica S.; Davies, Janine M.; Loree, Jonathan M.; Lim, Howard J.; Renouf, Daniel J.; Gill, Sharlene
Abstract : Introduction: With an increasing number of systemic therapy options for hepatocellular carcinoma (HCC), optimal sequencing is an important consideration. There remains limited real-world data about the eligibility of patients for second-line therapies in advanced HCC. We characterized real-world eligibility and use of second-line therapies post sorafenib. Materials and Methods: We identified all patients with advanced HCC who received ≥1 cycle of first-line sorafenib between January 1, 2014 and December 31, 2017 in British Columbia, Canada. All patients were Child-Pugh class A for initiation of sorafenib. Baseline characteristics and clinical outcomes were reviewed. Eligibility for second-line therapy was determined using the RESORCE and CELESTIAL study entry criteria. Results: Of 144 patients with advanced HCC who received ≥1 cycle of first-line sorafenib, median age was 65.3 years (range, 32.2 to 83.4 y) and 85% were male. Median duration of sorafenib was 2.6 months. Twelve patients (8%) received second-line treatment but 37 patients (26%) were eligible for second-line therapies based on inclusion criteria from recent registration trials. Primary reasons for ineligibility included ECOG ≥2 (58%), and deterioration to Child-Pugh status B (28%). On Cox regression, improved survival was associated with better ECOG and recurrent disease after initial locoregional therapy. Eligibility for second-line treatment was associated with improved median overall survival from end of first-line treatment (8.5 vs. 5.1 mo; P <0.01). Conclusions: Only a minority of real-world patients with advanced HCC were eligible for second-line therapies based on trial criteria. Given the high rate of attrition, improved first-line treatment options are urgently needed.